Local Flaps in Central Facial Basal Cell Carcinoma Reconstruction - Mehneet; Bhushan Kathuria; Saral Ahuja (Medicine and Medical Research: New Perspectives Vol. 10, 2024)
Background: Basal cell carcinoma is the most common skin cancer seen worldwide. It is a slow-growing tumour that rarely metastases. Although basal cell carcinoma is rarely lethal, it can cause substantial harm and disfigurement to adjacent tissues if treatment is delayed. The treatment of choice is surgical excision, followed by primary repair of the defect. Advancement flaps, nasolabial flaps and forehead flaps are the flaps that are frequently utilized for basal cell carcinoma of the face. Aim: The purpose of this chapter is to describe the different types of local flaps that can be used for reconstruction after resection of facial basal cell carcinoma along with their advantages and disadvantages. Methods and Results: This is a retrospective analysis of patients who had primary reconstruction utilizing local fasicocuataneous flaps after surgical excision of facial basal cell carcinoma at our institute from April 2023 to December 2023. Patients who underwent surgical excision of basal cell carcinoma followed by reconstruction with different local fasciocutaneous flaps were taken and analyzed based on flap uptake and healing. The patients were followed up for 6 months post-surgical excision with flap repair and all of them showed acceptable functional and cosmetic results. Conclusion: Local flaps after basal cell carcinoma surgery yield good results for facial reconstruction. Depending on the area involved, different flap techniques can be used to improve cosmetic outcomes and patient satisfaction.